Identification of total carotenoids and β-carotene content in local sweet potato (Ipomoea Batatas) for Halal pharmaceutical industry - Hussein, Suhair; Jaswir, Irwandi; Jamal, Parveen; Othman, Rashidi (2014)
Five varieties of sweet potato tuber in Malaysia, have been studied for their total carotenoid contents and βeta- carotene content through spectrophotometry and high performance liquid chromatography HPLC analysis. This study was conducted to compare carotenoids content in local orange, yellow, purple and white sweet potato tuber pulp. UV-spectrophotometryanalysis revealed that the orange sweet potato tuber flesh had the highest both β-carotene content and total carotenoid concentrations comparing to other sweet potato tuber flesh colors. Malaysian orange sweet potato showed the highest values of total carotenoid content and β-carotene concentration while white sweet potato showed the lowest levels of total carotenoid content and beta-carotene. In general, results of this study revealed that carotenoid content can differ with type of sweet potatoes flesh tuber. This study aimed to evaluate the high nutritional value of local sweet potatoes in Malaysia and their potential use in halal Pharmaceutical Industry.